3(x+1)-5=3x=-2

Simple and best practice solution for 3(x+1)-5=3x=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+1)-5=3x=-2 equation:



3(x+1)-5=3x=-2
We move all terms to the left:
3(x+1)-5-(3x)=0
We add all the numbers together, and all the variables
-3x+3(x+1)-5=0
We multiply parentheses
-3x+3x+3-5=0
We add all the numbers together, and all the variables
-2!=0
There is no solution for this equation

See similar equations:

| -3x+7(x-8)=-8 | | 7x/2-2=26 | | 9/5x=8 | | 4x+4/5=11/5 | | (9j+7)(8j+5)=0 | | 5x-2(2x-7)=(3x-1)+7/2 | | 4x4/5=11/5 | | 15=23x;x= | | 15x+150=480 | | 16.5/5.5=10.5/k | | -4/20x=18 | | 16b+14=–12−10b | | 20^2x-8=85 | | 4x4/5=21/5 | | 3/4.5=7/k | | 2h-15=25 | | -6/11x=14 | | 35h^2+33h=0 | | 15-4m-3m=m-8+7 | | 2(4x+5)=10x+2 | | -14-7w+10=8w+14-3 | | 16/16x=18 | | x/300=80/240 | | 3/x+1=6/x-7 | | 14x=5;x= | | -10z-14-8z=7-17z-12 | | 10−3p=–10−4−6p | | -10y+14y-21=-6y+23-12y | | x+2/2x-3=-3 | | 6-x-3+4=4(x-2) | | 3x+55=136 | | 8/1x=3 |

Equations solver categories